Efektivitas Assessment Peripheral Vascular Access Device (PVAD) terhadap Pencegahan Plebhitis - Sulistyorini Sulistyorini; Wiwin Yuli Triana; Nurul Chayatin; Diah Priyantini; Daviq Ayatulloh; Nursalam Nursalam; Ilya Krisnana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effectiveness of the Peripheral Vascular Disease Access Device (PVAD) assessment for the prevention of phlebitis. The method used is a literature review by searching for articles in the Scopus, ScienceDirect, CINAHL, Pubmed, Oxford, and SAGE databases. The results showed that patient assessment on intravenous therapy is helpful for patients undergoing intravenous therapy. Assessment made during insertion can increase the safety of administering intravenous therapy. Nurses' perceptions of the safety of intravenous administration are increasing. Some of the literature states that the assessment does not have a standard. This assessment is appropriate for identifying the need for intravenous therapy and facilitating intravenous therapy intervention. An understanding of the administration of intravenous therapy supports the implementation of the assessment. In conclusion, peripheral vascular access device (PVAD) assessment has clinical value in screening for phlebitis prevention. Keywords: Phlebitis Prevention, Assessment, Peripheral Devices